Toward Developing a Climatology of Fire Emissions in Central Asia - Yun Hee Park; Irina N. Sokolik (Air, Soil and Water Research, 2016)
Fire emissions are a significant mechanism in the carbon cycling from the Earth's surface to the atmosphere, and fire behavior is considerably interacted with weather and climate. However, due to interannual variation of the emissions and nonlinear smoke plume dynamics, understanding the interactions between fire behavior and the atmosphere is challenging. This study aims to establish a climatology of the fire emission in Central Asia and has estimated a feedback of fire emissions to meteorological variables on a seasonal basis using the Weather Research and Forecasting model coupled with Chemistry. The months of April, May, and September have a relatively large number of pixels, where the plume height is located within the boundary layer, and the domain during these months tends to have unstable conditions at the strongest smoke, showing a lower percentage of stable conditions. From the seasonal analysis, the high fire intensity occurs in the summer as smoke travels above the boundary layer, changing temperature profile and increasing the water vapor mixing ratio.